2009
DOI: 10.1016/j.ijer.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An ethnographic study of the friendship patterns of international students in England: An attempt to recreate home through conational interaction

Abstract: This paper reports findings from an ethnographic study into the adjustment experience of a group of postgraduate international students at a university in the South of England. Friendship emerged as a major theme in this study; of particular importance to students was the desire and need to mix with conational friends. This desire was driven by the urge to obtain the comfort offered by shared language, shared heritage and access to instrumental support. It was also informed by fear of discrimination and compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 33 publications
(39 reference statements)
3
90
0
8
Order By: Relevance
“…Similarly, Dunne (2009) found that at an Irish university local students requested that their international counterparts lived in separate residences; a move which limited interaction between them. The same pattern of segregation was observed in dining halls and other social settings (Brown 2009). …”
Section: Integration Of Diverse Students At University Residencessupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly, Dunne (2009) found that at an Irish university local students requested that their international counterparts lived in separate residences; a move which limited interaction between them. The same pattern of segregation was observed in dining halls and other social settings (Brown 2009). …”
Section: Integration Of Diverse Students At University Residencessupporting
confidence: 70%
“…Some studies suggest that living arrangements in several university residences were seen as a way of segregating diverse students (Ward and Masgoret 2004;Brown 2009;Peacock and Harrison 2009;Thornton et al 2010). Thornton et al (2010) reveal that at certain universities in the UK and India, the authorities usually allocated international students to specific residences.…”
Section: Integration Of Diverse Students At University Residencesmentioning
confidence: 99%
“…This is usually a time of intense socialisation, in which the international students get to know each other, form groups, share information and advice (Hendrickson, Rosen, & Aune, 2011). Most are inevitably drawn to co-nationals, with whom communication is much simpler at a time of need (Brown, 2009). Many are also attracted to other foreign students, particularly other Erasmus participants (see de Federico de la Rúa, 2008).…”
Section: Angela's Social/personal Experiencesmentioning
confidence: 99%
“…In response to this gap in knowledge, this paper examines the factors that influence isolation; but, more importantly, it considers the various coping mechanisms that may be adopted by doctoral students, as well as what institutions could do to tackle this issue. Ali and Kohun (2006;2009) offer useful indicative insights into loneliness among doctoral students; however, much of their work is theoretical, based principally on a review of related literature, or it is developed from institutional metrics and survey data from a relatively small sample. The themes of loneliness and friendship networks are often examined from the international student perspective with a specific focus on master's students' experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also tried to understand what caused such feelings and how these could be mitigated. Mori's (2000) study found high levels of stress in Asian students triggered by interpersonal problems; Bradley's (2000) survey of the needs of international students indicated a high degree of mental health problems, caused by isolation, and depression; and in a recent study, Brown (2009) highlighted the impact of loneliness on both well-being and friendship networks. It can be seen that while a substantial body of literature exists exploring international students' experiences of loneliness and friendships' networks, previous research has not focused on doctoral students.…”
Section: Introductionmentioning
confidence: 99%